Pengaruh Modifikasi Permukaan Piston terhadap Emisi Gas Buang Motor Bakar Kapasitas 100 cc - Gennarki Dini Setyawan Putra; Khambali Khambali (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Technological advances in motorized transportation are progressing rapidly, making motorized vehicles the main mode of transportation. The increasing number of motorized vehicles in society results in a significant increase in exhaust emissions. Combustion in vehicle engines is not always perfect, producing exhaust gases containing compounds harmful to human health, such as carbon monoxide (CO), hydrocarbons (HC), carbon dioxide (CO2), and nitrogen oxides (NOx). This study investigates the effect of variations in piston dome shape on exhaust emissions in a 100cc internal combustion engine using RON 90 fuel. The goal is to find the optimal compression ratio to produce cleaner exhaust emissions. The research data are presented in tabular form and analyzed using one-way ANOVA and graphs. The results showed a significant reduction in CO and HC emissions at all engine speeds (1000, 2000, 4000, and 5000 rpm) with variations in piston dome shape. The reduction in CO emissions ranged from 55.07% to 85.73%, while the reduction in HC emissions ranged from 54.14% to 86.10%. These results suggest that variations in piston dome shape can be an effective solution to minimize harmful exhaust emissions in internal combustion engines.